A Narrative Review of Myxoid Solitary Fibrous Tumor: A Rare Benign Maxillofacial Tumor - Kavitha Anbalagan; Marzuki Zainal Abidin; Shahida Mohd-Said (TALENTA, 2025)
Solitary fibrous tumor (SFT) is a relatively rare mesenchymal neoplasm characterized by spindle cells exhibiting fibroblastic differentiation. The neoplasm was initially identified in the pleura but had later been recognized in various human anatomical areas. In addition, it typically features disorganized spindle cells, varying cell density, collagen-rich stroma, and slender branching blood vessels. Several studies have shown that myxoid SFT with a significant myxoid stroma is exceedingly rare, with less than 15 cases reported. Approximately 20% of SFT often occurs in the head and neck, including the meninges. The extracranial head and neck area have been reported to be the most common areas, particularly the sinonasal tract, oral cavity, and deep soft tissues, such as the orbit. Therefore, this narrative review aims to describe the distinctive features of SFT to assist clinicians in identifying their rarity.